Pengembangan Media Pembelajaran Komik Digital pada Pembelajaran IPS Materi Kegiatan Ekonomi Kelas IV SD Negeri 43 Pangkalpinang - Nur Afifah; Maulina Hendrik; Fandi Nugroho (JBES (Journal Basic Education Skills), 2024)
This research is motivated by students’ lack of understanding of economic activities due to the inappropriate use of learning media to describe economic activity material and its relationship with various fields of work around where they live. This research aims to produce digital comic learning media for social studies learning material for class IV economic activities at SD Negeri 43 Pangkalpinang that is feasible and practical. The type of research used is research and development (R&D) using the ADDIE (Analyse, Design, Develop, Implement, and Evaluate) development model. The data collection techniques used were interviews, questionnaires, and tests. The data analysis technique is quantitative descriptive using a Likert scale, the Kolmogrov-Smirnov test, and a paired t-test. The subjects in this research were fourth-grade students at SD Negeri 43 Pangkalpinang. This research produces digital comic learning media that is “feasible and practical." This can be seen from the material expert validation percentage results of 88.88% and the media expert validation results of 94.66%. Furthermore, the results of the practicality of learning media from the results of student questionnaire responses in small classes were 97.33%, and the results in large classes were 97.65%. Based on the pretest and posttest results, the average pretest score was 51.66, and the average posttest value was 81.00. Based on the paired t-test results, it was obtained that t_count>t_le was 15.832>1.699, meaning that Ha was accepted.